The stranger [compact disc, unabridged] - Läckberg, Camilla, 1974- (Läckberg, Camilla, 1974- Patrik Hedström mysteries, 2013)
The death of a local women in a car crash marks the end of a quiet winter for detective Patrik Hedström. Meanwhile, a reality TV show is being shot in the town, and when a drunken party ends with an unpopular contestant's murder, the cast and crew are obvious suspects. Ratings soar as the country tunes in to a real-life muder mystery, and Patrik tackles his toughest investigation yet.